STRATEGI REBRANDING UMKM KERIPIK DESA CELAWAN DALAM MEMPERKUAT PERAN MEDIA DIGITAL UNTUK MENINGKATKAN DAYA SAING DI ERA DIGITAL: Strategi Rebranding UMKM Desa Celawan dalam Memperkuat Peran Media Digital Untuk Meningkatkan Daya Saing di Era Digital - Ratih Silviany; Ahmarani, Putri; Syafriani, Nurul; Idam, Zahratul (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2025)
This study originates from the need of the Keripik Desa Celawan MSME to enhance its competitiveness through strengthened brand identity and more structured utilization of digital media. The digital shift offers broader marketing opportunities; however, many micro-enterprises still struggle to adapt due to limited promotional strategies and insufficient use of available technologies. This study aims to formulate an applicable rebranding strategy and to evaluate the effectiveness of digital media in increasing the visibility of local chip products. A qualitative descriptive approach was employed through field observations and in-depth interviews with the business owner and one employee directly involved in production and marketing. Through thematic analysis, three major findings emerged: first, rebranding significantly improves product perception by refining packaging quality and strengthening visual identity; second, the use of digital media particularly social media platforms and Google Maps location successfully expands product accessibility and consumer reach; third, continuous mentoring enhances the digital literacy of MSME actors, enabling them to sustain independent promotional activities. Overall, this study confirms that integrating rebranding efforts with digital marketing strategies not only elevates product visibility but also strengthens the long-term sustainability of community-based micro enterprises